Bach Perspectives, Volume 7: J. S. Bach's Concerted Ensemble Music : The Concerto - Butler, Gregory (Book collections on Project MUSE., 2008)
The creativity of J.S. Bach is so overwhelming that his compositions in some genres can risk eclipsing his work in others; his glorious choral works, profound organ compositions, and exquisite solo compositions for violin and cello have historically attracted the most attention. Volume 7 of Bach Perspectives aims to restore Bach's concertos to their rightful place of honor. Continuing the reevaluation of these musical compositions, Gregory Butler focuses on Bach's Concerto for Harpsichord and Strings in E Major (BWV 1053) as a pastiche created by a process of assemblage of three earlier heterogeneous movements. Pieter Dirksen, on the basis of his study of the source history of the Concerto for Harpsichord and Strings in F Minor (BWV 1056), concludes that it represents a transcription of an earlier violin concerto in G minor. David Schulenberg investigates the generic ambiguity of the concerto at the beginning of the eighteenth century and how it gradually diverges from the sonata as a distinct genre. Completing the volume is Christoph Wolff's general examination of the siciliano as a slow movement in Bach's concertos and its implications for the source history of his Concerto for Harpsichord and Strings in E Major (BWV 1053) [Publisher description].